Analisis Wacana Visual Dalam Iklan Samsung Galaxy S24 Versi Lyodra Ginting Di Youtube: Love In Translation - Hotmauli Sri Yulina; Novita Sari; Oktaviana Simanjuntak; Mustika Wati Siregar (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to analyze the visuals of Lyodra Ginting's version of the Samsung advertisement on YouTube. This research uses a qualitative descriptive method. Data collection techniques include documentation and data sources from YouTube and Samsung Indonesia. Data analysis techniques use the concept of visual hierarchy theory. The results of this research are advertising which has attracted the interest of many researchers because hierarchy theory provides an in-depth analysis of the visual elements that enhance the image of a product